The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.ymssp.2019.106305
|View full text |Cite
|
Sign up to set email alerts
|

Transient flow analysis in a Roots blower: Experimental and numerical investigations

Abstract: It is widely acknowledged that rotary positive displacement machines exhibit highly unsteady flow fields that affect their performance. The presence of the operational clearances impacts this unsteady flow field and further affects the performance. However, the exact nature of these unsteady flow mechanisms remains largely unknown that necessitates both detailed experimental investigations and computational modelling. Thus, the present study employs both optical visualization and unsteady Reynolds-Averaged Nav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…The phase-lock condition required every pair of images to be identical to each other at exact the same crank angle. However, the images change in angular position slightly from cycle to cycle because of fluctuations in the rotational speed [26]. We found that the images match each other after every 10 cycles.…”
Section: Experimental Setup and Data Processingmentioning
confidence: 68%
See 4 more Smart Citations
“…The phase-lock condition required every pair of images to be identical to each other at exact the same crank angle. However, the images change in angular position slightly from cycle to cycle because of fluctuations in the rotational speed [26]. We found that the images match each other after every 10 cycles.…”
Section: Experimental Setup and Data Processingmentioning
confidence: 68%
“…The double-pulse laser (K) and double shutter camera (M) with the resolution of 2048 × 2048 pixels were used to take every pair of images at a short interval of 2-50 µs that was depended on the maximum particle velocity in the flow field. The equipment used for measurements was introduced in detail in the previously published paper by the authors [9,25,26]. For the measurement of gap flow field, following changes were made to the test set-up: Firstly, the microscope lens Model K2 (Infinity photo-optical, Centennial, CO, USA) was equipped on the double-shutter camera to magnify the tip gap (see Figure 3).…”
Section: Experimental Setup and Data Processingmentioning
confidence: 99%
See 3 more Smart Citations